UTILIZATION OF COMMUNITY SOCIAL CAPITAL TO FIGHT OFF CHILD SEXUAL BUSINESS - Aditya Rizky Nugroho (Airlangga Development Journal, 2023)
Forms of verbal sexual abuse of children are inviting, seducing, insulting and threatening. Non-verbal forms of child sexual abuse include touching, stroking, hugging, forcing and attacking. Social capital is very important and very necessary to be utilized as an antidote to child sexual bullying. Social capital is a component and core element of the support system. A support system is needed, in synergy with each other and consisting of all stakeholders: Central Government, Ministries, Regional Government, Regional Heads, POLRI, Sub-Departments, School Principals, Teachers, Homeroom Teachers, Guidance Teachers, RT/RW Heads, Parents, Religious Leaders , Community Figures, Non-Governmental Organizations and all members/components of society. POLRI, Schools (Principals, Homeroom Teachers, Counseling Teachers, Teachers), Parents, Religious Leaders and Community Figures have the duty and responsibility to explain to and train children to be able to behave and be skilled in behaving alertly to the dangers/threats of child sexual abuse.